Pengaruh Kualitas Pelayanan Terhadap Kepuasan Anggota Dan Dampaknya Pada Loyalitas Anggota Sebagai Pelanggan - Said Iqbal, Muhammad; Wahyudin, Wahyudin (Coopetition : Jurnal Ilmiah Manajemen, 2025)
PRIMKOPKAR Cooperative of Perum Perhutani Unit III West Java and Banten has experienced a decline in the number of members making transactions. This condition is assumed to be caused by unsatisfactory service quality, leading to loyalty. Data were collected through interviews, questionnaires, observation, and literature studies, and processed using SPSS. The population in this study consisted of 1,012 members, with a sample of 100 respondents. Data analysis techniques included descriptive analysis and path analysis. The results of the path analysis show that: (1) the service quality variable (X) has a significant effect on customer satisfaction (Y₁) with a path coefficient (β) of 0.307 and a significance level of < 0.001 (p < 0.05); (2) the customer satisfaction variable (Y₁) significantly affects customer loyalty (Y₂) with a path coefficient (β) of 0.421 and a significance level of < 0.001 (p < 0.05). Furthermore, the indirect effect of service quality on customer loyalty through customer satisfaction is 0.129. Keywords: Service Quality, Customer Satisfaction, Customer Loyalty and Cooperative